The alga Sargassum spp. as alternative to reduce egg cholesterol content - Carrillo, Silvia; Bahena, A.; Casas, M.; Carranco, M. E.; Calvo, C. C.; ?vila, E.; P?rez-Gil, F. (Cuban Journal of Agricultural Science, 2012)
In order to determine the effect of the addition of the sea alga Sargassum spp. on the egg cholesterol content in the diet of laying hens, 225 Leghorn hens were used at 19 weeks of age and distributed randomly into five treatments (0, 2, 4, 6, and 8 % of the sea alga). The experiment lasted five weeks, during which the productive variables were recorded. The physical quality was assessed in 75 eggs per treatment. Thirty-five pieces of each treatment were collected for the analysis of the egg cholesterol (yolk + albumin) through gas chromatography. The data were analyzed through ANOVA and the test of Tukey was applied to compare the means (P < 0.05). The results showed that with 4, 6, and 8 % of the sea alga the egg production was reduced and the yolk color was increased. The cholesterol concentrations (mg 100 g-1 fresh egg) were 416.28 (0 % sea alga), 396.77 (2 % sea alga), 363.35 (4 % sea alga), 309.05 (6 % sea alga), and 338.76 (8 % sea alga). It was concluded that the addition of 4, 6, and 8 % of the alga Sargassum spp. in the diet of laying hens reduces significantly the egg cholesterol content and affects favorably the yolk color. Key words: sea algae, eggs, lipids, hypocholesterolemic properties